Facts and Artefacts of Religious Freedom in Ukraine - Olena Leshchynska (Vasyl Stefanyk Precarpathian National University, 2019)
The article looks at the psychological conditions in which a modern person can rightly exercise their right to religious freedom and the preconditions for their involvement with the totalitarian (destructive) religious cults. The central issues of the article are as follows: the concept of spiritual need as a socially recognized psychic norm; the phenomenon of psychotherapeutic potential of the religious community; religiosity and spirituality. It has been proved that personality maturity is the precondition and the basis for healthy spirituality. A marked artefact of religious freedom in Ukraine is individuals' involvement with destructive cults, which may lead to psychic and social dependence. Also the article presents the results of an empirical research involving a mass psychosemantic survey carried out in order to find how this religious problem is reflected in the mass consciousness of Ukrainians and in-depth interviews with people who have experienced psychic dependence on the cult.